Unwanted childbearing and household food insecurity in the United States. Issue 2 (19th August 2014) - Patel, Shivani A.; Surkan, Pamela J.
Abstract: Household food insecurity is a population health concern disproportionately affecting families with children in the United States. Unwanted childbearing may place unanticipated strain on families to meet basic needs, heightening the risk for household food insecurity. We investigated the association between mother's and father's report of unwanted childbearing and exposure to household food insecurity among children residing in two‐parent households in the United States. Data from the Early Childhood Longitudinal Study – Birth Cohort, a nationally representative cohort of US children ( n  ∼ 6150), were used to estimate the odds of household food insecurity when children were aged 9 months and 2 years, separately, based on parental report of unwanted childbearing. The majority of children were reported as wanted by both parents (74.4%). Of the sample, report of unwanted childbearing by father‐only was 20.0%, mother‐only was 3.4% and joint mother and father was 2.2%. Household food insecurity was higher when children were 9 months compared with 2 years. In adjusted models accounting for confounders, children born to mothers and fathers who jointly reported unwanted childbearing were at higher odds of exposure to household food insecurity at 9 months [adjusted odds ratio (AOR) = 3.31; 95% confidence interval (CI): 1.97, 5.57] and 2 years (AOR = 2.52; 95% CI: 1.12, 5.68). In two‐parent households, we found that children raised by parents reporting unwanted childbearing were more likely to be exposed to food insecurity and potentially related stressors. Further studies that prospectively measure wantedness before the child's birth will aid in confirming the direction of this association.